1997
DOI: 10.1007/bf00788521
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial length-force relationship in end stage dilated cardiomyopathy and normal human myocardium: analysis of intact and skinned left ventricular trabeculae obtained during 11 heart transplantations

Abstract: The present study shows that except for diastolic stiffness and a smaller relative force increment after any length step in DCM the Frank Starling mechanism is still present in isolated human left ventricular DCM- as in NDH-myocardium. The current study does not allow to decide whether in skinned myocardium the smaller percent decline in force after reduction of activator calcium concentrations in DCM is caused by an increased calcium sensitivity at short sarcomere lengths or decreased sensitivity at long sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
22
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
9
22
0
1
Order By: Relevance
“…2 Human DCM hearts were also found to have higher-than-normal passive stiffness. 31 In the present work, the relationship between titin-derived passive stiffness and non-titin-based stiffness (ECM, intermediate filaments) was found to be altered in nonischemic DCM HHs: the relative contribution of titin to total passive stiffness was greatly reduced compared with that in control-donor HHs. Two recent studies suggested that failing human 19 and dog 21 hearts adjust their passive stiffness by titin-isoform switching.…”
mentioning
confidence: 83%
“…2 Human DCM hearts were also found to have higher-than-normal passive stiffness. 31 In the present work, the relationship between titin-derived passive stiffness and non-titin-based stiffness (ECM, intermediate filaments) was found to be altered in nonischemic DCM HHs: the relative contribution of titin to total passive stiffness was greatly reduced compared with that in control-donor HHs. Two recent studies suggested that failing human 19 and dog 21 hearts adjust their passive stiffness by titin-isoform switching.…”
mentioning
confidence: 83%
“…In human heart failure, the Frank-Starling mechanism and LDA have been reported to be normal [56], reduced [94,96,13], or lost based on the weak increase in Ca 2+ sensitivity of myofibrils after stretch [80]. Alterations of cardiac contractility, as a consequence of remodeling of the whole heart, have been described also in a rat model after myocardial infarction (MI) [6].…”
Section: Consequences Of Alterations In Lda Heterogeneity On Cardiac mentioning
confidence: 99%
“…As we mentioned in the Introduction, experimental data on the mechanical activity in cellular or multicellular human myocardial preparations are very limited. In few experimental works performed in the nineties of the 20th century, contraction of papillary muscle and trabeculae from the ventricles of the human hearts were studied in isometric mode [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] and only two papers report on contractions under mechanical loads [47,55]. Below, in our simulations we compare, wherever possible, the data of numerical experiments with the results from the listed works.…”
Section: Figmentioning
confidence: 99%